Understanding osteoporosis knowledge and health beliefs in maternity nursing students: a cross-sectional study - Faeda A. Eqtait; Bahaaeddin M. Hammad; Ahmad J. Ayed; Basma S. Salameh; Imad H. Fashafsheh; Anas H. Khalifeh; Mohammed A.L. B.ashtawy (PLoS ONE, 2025)
Background Osteoporosis is a growing health problem worldwide. Increasing awareness, knowledge, and promoting healthy behaviors in regard to osteoporosis and related risk factors are important targets in preventive behaviors. Aim This study aimed to investigate maternity nursing students’ knowledge, beliefs, and preventive behaviors regarding osteoporosis. Methods A cross-sectional study was conducted on a convenience sample of maternity nursing students at a private university in Palestine. The researchers collected data through self-administered questionnaires, included the Osteoporosis Knowledge Assessment Tool and Health Belief Scale. The collected data was analyzed using SPSS version 26, employing both descriptive and inferential statistics. Results A total of 139 students completed the questionnaire with a response rate of 92.6%. The students demonstrated an average level of knowledge about osteoporosis with a mean score of 10.38 (SD = 4.48). Common risk factors identified were caffeine intake (69.9%), smoking (55.9%), and low calcium intake (46.3%). The mean Osteoporosis Health Belief Scale score was 124.87 (SD = 24.21), with high perceived benefits for exercise (22.43 ± 5.61) and calcium intake (21.01 ± 5.11) but low susceptibility (13.26 ± 4.77). Knowledge was significantly higher in fourth-year students (p = 0.034) and overweight participants (p = 0.020). Calcium supplementation predicted health belief scores (p = 0.011), while academic year and sun exposure had no significant impact. Conclusion The current study confirmed that maternity nursing students had average knowledge about osteoporosis. There is a gap between the students’ beliefs about osteoporosis and their daily lifestyle. Therefore, a special attention should be paid to raise the level of osteoporosis awareness among nursing students through health education program. as well as broader integration of osteoporosis in nursing curricula is urgently warranted.